PENGARUH PENERAPAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN BERMAIN PIANIKA DI KELAS VA SDN 28 PONTIANAK UTARA - Saputra, Angga (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract  This Effect of Audio-Visual Media in Play Skills of Pianika On Music Art Lesson, Fifth Degree SDN 28th North Pontianak research has an aims to otain information about the effect of audio-visual media on play skills of pianika  on results of students education in fifth degree SDN 28th north Pontianak. This research using experiment methods with One-Group Pretest-Postest Design. Based on statistical calculation, the average pretest was 80.68 with the lowest score was 69.60, and the highest score was 86.6, while the average post-test score was 84.68 with the lowest score was 78.8 and the highest score was 92.4. Based on statistical calculations, known that the results of student learning using Audio-Visual Media was higher than without the use of audio visual media. This meant that learning using the Audio-Visual Media gives a great influence on the outcomes for fifth degres students of 28th North Pontianak